Molecular detection of endosymbiont bacteria Wolbachia in bedbug species Cimex lectularius from Vidarbha region of India - Siddiqui SS; Raja IA (International Journal of Life Sciences, 2015)
Wolbachia are maternally inherited bacterial endosymbionts that found in different arthropods. It is now well known that they induce reproductive phenotypic manipulations like feminization, thelytokous parthenogenesis, male killing and cytoplasmic incompatability in their arthropod hosts. Although diverse insects are infected with Wolbachia bacteria and generally for their insect hosts, it is regarded as facultative/parasitic endosymbiont bacteria. The Wolbachia strain, designated as wCle associated with the bedbug Cimex lectularius was shown to be vital for the growth of host’s and reproduction via provisioning of B vitamins. Previously the infection of endosymbiotic Wolbachia bacteria has been shown to the colonies of the human bed bug, Cimex lectularius L. (Heteroptera: Cimicidae) cultured in the laboratory, but no information exists regarding the infection status in natural populations in India. We assayed Cimex lectularius populations from different areas of Vidarbha region (Akola, Amravati, Chandrapur,Nagpur), Maharashtra, India for Wolbachia infection. Detection was done by the polymerase chain reaction (PCR). Wolbachia infections were prevalent in all populations assayed (75–100%). Higher rate of Wolbachia infections were found in bedbugs of Vidarbha region of India, which indicates importance of this association. The characterization of these Wolbachia strains provides a deeper approach into this interaction, which is essential for further studies. The potential utility of Wolbachia for another bed bug control strategies is discussed.